2018
DOI: 10.1080/15384101.2018.1547001
|View full text |Cite
|
Sign up to set email alerts
|

Accurate delineation of cell cycle phase transitions in living cells with PIP-FUCCI

Abstract: Cell cycle phase transitions are tightly orchestrated to ensure efficient cell cycle progression and genome stability. Interrogating these transitions is important for understanding both normal and pathological cell proliferation. By quantifying the dynamics of the popular FUCCI reporters relative to the transitions into and out of S phase, we found that their dynamics are substantially and variably offset from true S phase boundaries. To enhance detection of phase transitions, we generated a new reporter whos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(154 citation statements)
references
References 69 publications
(90 reference statements)
5
148
1
Order By: Relevance
“…According to the many‐for‐all model, observation of coupling between cell cycle phases would imply that phase‐controlling factors are relatively more abundant in certain cell types. Third, we employ a more accurate method of measuring cell cycle phase durations based on appearance and disappearance of PCNA foci during S phase and validate these results with an orthogonal measurement of phase duration (Grant et al , ; Appendix Fig S2B and C; Chao et al , ; Grant et al , ). Previous studies employed the FUCCI reporter system to distinguish G1 and S‐G2‐M cells, but this system is known to give unclear cell cycle phase boundaries (Wilson et al , ; Grant et al , ).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…According to the many‐for‐all model, observation of coupling between cell cycle phases would imply that phase‐controlling factors are relatively more abundant in certain cell types. Third, we employ a more accurate method of measuring cell cycle phase durations based on appearance and disappearance of PCNA foci during S phase and validate these results with an orthogonal measurement of phase duration (Grant et al , ; Appendix Fig S2B and C; Chao et al , ; Grant et al , ). Previous studies employed the FUCCI reporter system to distinguish G1 and S‐G2‐M cells, but this system is known to give unclear cell cycle phase boundaries (Wilson et al , ; Grant et al , ).…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, the lack of correlation was not due to the sampling frequency chosen, as the correlation coefficients did not depend on the sampling frequency in the range that was used (Appendix Fig S6). To confirm these results, we validated the lack of correlation among cell cycle phases in an independent fluorescent reporter system (Grant et al, 2018;Appendix Fig S2B and C, and Table S1). A statistical power analysis revealed that our sample size would be adequate to detect significant correlations, if present (Materials and Methods).…”
Section: Cell Cycle Phase Durations Are Uncoupled Under Unstressed Comentioning
confidence: 72%
See 1 more Smart Citation
“…We used live cell imaging of fluorescently tagged protein biosensors to compare the length of available MCM loading time between the first and second cell cycles after G0. We imaged an RPE1 cell line stably expressing three fluorescent fusion proteins: 1) full length Cdc6 fused to mVenus (Segev et al, 2016), 2) Proliferating Cell Nuclear Antigen (PCNA) fused to mTurq2 to track cell nuclei and the borders of S phase (Burgess et al, 2012;Grant, Kedziora et al, 2018), and 3) a CDK kinase activity sensor fused to mCherry (Hahn et al, 2009). This kinase sensor was previously established to report CDK2 activity in G1 and early S phase and both CDK2 and CDK1 activity in S and G2 phase; it is not a direct reporter of CDK4/6 activity (Spencer et al, 2013;Schwarz et al, 2018).…”
Section: G0 Cells Re-entering the First Cell Cycle Load MCM To Licensmentioning
confidence: 99%
“…The RPE1 cells with doxycycline inducible Cyclin E1 and the RPE1 cells with doxycycline inducible Cdt1 and stable Cdc6 WT or Cdc6-mut were described previously (Matson et al, 2017). The pLenti-PGK hygro PCNA-mTurq2 was described previously (Grant et al, 2018). The CSII-EF zeo DHB-mCherry CDK activity reporter was a gift Dr. Sabrina Spencer.…”
Section: Dna Cloning and Cell Linesmentioning
confidence: 99%